An investigation into the geometric parameters affecting field uniformity in four pole magnetisers - Bartolo, James Borg; Klimczyk, Piotr; Tiwisina, Kai; Denke, Patrick; Siebert, Stefan; Gerada, Christopher (IOS Press, 2015)
In recent years, the field-metric method for measuring the joule losses set up in an electrical steel laminate when subjected to a rotating field has gained popularity. The ideal geometry of the magnetiser required to set up such a field is still however the subject of much debate. The work presented in this paper aims at providing some useful guidelines which might be considered when undertaking the construction of the simplest of such magnetizing setups having four salient poles excited by a two phase system and using a square sample. A 3D model for this rotational power loss tester was simulated for different pole geometries with the induction uniformity being assessed for every alteration.